Preliminary Analysis of e-Government Implementation and Readiness in Sikka Regency: A Foundational Study for the AVELINE Evaluation Model - Agustinus Lambertus Suban (Technologia Journal, 2025)
This study presents a preliminary analysis of e-government implementation and readiness in Sikka Regency, East Nusa Tenggara, as the empirical foundation for developing the AVELINE Evaluation Model a context-sensitive framework designed to assess e-government maturity in developing local governments. Using a mixed-methods approach, the research integrates quantitative survey data from 120 respondents across 15 government agencies with qualitative insights from in-depth interviews and document analysis. The findings indicate a moderate overall readiness index (3.04 out of 5), reflecting partial progress in digital transformation. Among the five assessed dimensions, policy and governance readiness scored highest (3.47), while citizen engagement and human resource readiness remained lowest (2.76 and 2.85, respectively). The study identifies key inhibitors such as limited ICT infrastructure, insufficient digital literacy, and fragmented inter-agency coordination, which hinder effective SPBE (Electronic-Based Government System) implementation. Conversely, strong policy commitment and emerging leadership support provide a foundation for improvement. Empirical results confirm significant correlations between infrastructure, human resources, and organizational readiness, emphasizing that technological success depends on institutional and socio-environmental factors. Theoretically, this research contributes to the development of the AVELINE Evaluation Model, integrating six dimensions Administrative, Viability, Environmental, Legal, Information, and Network readiness into a holistic tool for assessing e-government maturity. Practically, recommendations for infrastructure enhancement, human resource capacity building, and participatory governance. Overall, the findings highlight that digital transformation in Sikka Regency remains in a transitional phase technologically functional but organizationally fragile underscoring the need for a tailored, context-aware evaluation framework to guide sustainable e-government development in underdeveloped regions